Exit Interview and Self-disclosure: How Employees Reveal Personal Information and Feeling as They Leave the Organization - Soerjoatmodjo, Gita Widya Laksmini (Fakultas Psikologi Universitas Mercu Buana, 2014)
Improving employee relations for a better organizational climate can be approached in many ways, including by focusing on those who choose to leave the organization for various reasons. One way is conducting exit interview â an exchange of information between a representative of an organization and an employee who is leaving the organization. When conducted properly, it can serve as useful tools for improving people and the organization, as well as turnover reduction and retention tactic. Hence, it should be implemented as a part of the overall human resources management process. However exit interview is questionable in many situations. It is because exiting employees are reluctant to reveal their personal information and feeling, known as self-disclosure. In this research, semi-structure interviews are conducted to former employees of an organization on their experience in participating in exit interviews. The quality and texture of self-disclosure process experienced by each individual is captured through interpretative phenomenology analysis. Findings of this qualitative research identify themes disclosed by these former employees in their exit interviews and the process they experienced. It is hope that this research would contribute to better understanding on exit interviews and on how to improve employee relationship and organizational climate.